El papel de los bosques de arena blanca en la diversidad de anfibios de la Amazonia Oeste - Urrutia, Luis Alberto Giussepe Gagliardi (2020)
White sand forests of western Amazonia typically grow on poor quartz-rich sandy soils. They are characterized by thin trunks, low canopy and poor water retention. They are generally arranged as isolated patches inside a matrix of forests growing on richer clay soils. These specific conditions cause particular physiological and ecological responses, including adaptations and speciation. We know very little about the effects that these ecosystems have over animal communities, which led us to our main objective: To identify which is the contribution of white sand forests to the spatial structure of amphibian diversity in western Amazonia. To address it, we performed systematic samplings in three western Amazonia localities from Peru (Estación Biológica José Álvarez Alonso – EBJAA, Centro de Investigaciones Jenaro Herrera – CIJH y el río Blanco – RB), each separated from each other by 100 km. We designed 36 transects and evaluated the richness and abundance of amphibians during two years by sampling transects up to three times per year. We characterized white sand forests using soil texture by quantifying sand percentage. We also quantified canopy openness and leaf-litter mass. Using Nonmetric Multidimensional Scaling (NMDS), we found an effect of geographic distance over the amphibian community of each locality. Using NMDS values as a dependent variable and the environmental data as independent variables, we performed multiple regression analyses. Our results show that there is an effect of soil texture over the EBJAA and RB amphibian communities (although with lower probability on the latter); meanwhile, none of the evaluated environmental variables explains the amphibian community structure of CIJH. We identified a group of seven amphibians as specialists of white sand forests, sharing the use of phytotelmata or direct development in their reproduction. We registered new species for science from different genera and families (e.g., Allobates sp., Scinax sp., Chiasmocleis sp.), several of them closely associated with White sand forests. We described one of the new species (Allobates sp. nov.) as well as unknown aspects of the natural history of several other species and new geographic records of poorly known Amazonian species. We conclude that white sand forests are important factors that determine amphibian diversity at the local scale, but that their effect is idiosyncratic, depending of biogeographic, hydrologic and geologic factors. We also discover that there is a specialized amphibian fauna associated with white sand forests, which is characterized by using phytotelmata for tadpole development of having direct development.